Design And Prototype Fabrication of an Ash Cleaning Device for Grill Application - Rosli, Muhammad Amirul Aiman; Aslinda Saleh (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Cleaning ash from grills has always been a messy and time-consuming chore, especially when dealing with fine particles and stubborn burnt residues. This study set out to solve that everyday problem by designing, developing, and testing a more practical solution: a Multi-Sprayer Ash Vacuum Cleaner. This device combines the power of a vacuum suction system with a water spraying mechanism, making grill cleaning not only faster but also safer and more hygienic. The journey began by identifying user needs through surveys and background research. It became clear that users desired a tool that was easy to handle, effective in removing ash without spreading dust, and safe to use around heat. With those needs in mind, the project moved into the design phase using SolidWorks 2024, where several design iterations were simulated and refined. Special attention was given to integrating a DC motor-powered suction system and a water pump-fed multi-sprayer nozzle two core components that work together to dampen and remove ash with minimal effort. Once the design was finalized, a prototype was fabricated using a combination of 3D printing and manual assembly. It was then put through a series of functionality tests under simulated grilling conditions. The results confirmed that the device performed as intended: the sprayer effectively moistened hot ash to prevent it from becoming airborne, and the vacuum system removed the damp residue cleanly. Additional features such as a heat-resistant body, ergonomic handle, removable ash container, and water tank made the device even more practical for real-world use. Overall, this project successfully developed a functional and user-friendly ash vacuum cleaner that meets real user demands. It not only simplifies the post-grilling cleaning process but also demonstrates the value of combining mechanical design, simulation tools, and hands-on testing in solving practical problems through engineering.